2020
DOI: 10.1002/nau.24407
|View full text |Cite
|
Sign up to set email alerts
|

A timeline of female stress urinary incontinence: how technology defined theory and advanced treatment

Abstract: Background Prevailing theories and treatments of female stress urinary incontinence are built on 120 years of evolution in understanding the structure and function of the female bladder neck and urethra and of considering why treatments failed. In our management of patients, it is important to understand and appreciate how our management of female stress urinary incontinence has evolved and which treatments have prevailed as we advance our knowledge for future treatments. Aims The purpose of this review is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…DeLancey [ 20 ] delineated endopelvic fascia and anterior vaginal wall as the hammock-like supportive layer of urethra, which could stabilize and help to close urethra during cough. Sling, placing a supportive material behind urethra, had been a staple procedure for SUI and withstood the test of time [ 21 ]. Back to continence after RP, we hypothesized “hammock theory” still work on and preferred DF to be the critical structure (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…DeLancey [ 20 ] delineated endopelvic fascia and anterior vaginal wall as the hammock-like supportive layer of urethra, which could stabilize and help to close urethra during cough. Sling, placing a supportive material behind urethra, had been a staple procedure for SUI and withstood the test of time [ 21 ]. Back to continence after RP, we hypothesized “hammock theory” still work on and preferred DF to be the critical structure (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…DeLancey [20] delineated endopelvic fascia and anterior vaginal wall as the hammocklike supportive layer of urethra, which could stabilize and help to close urethra during cough. Sling, placing a supportive material behind urethra, had been a staple procedure for SUI and withstood the test of time [21] . Back to continence after RP, we hypothesized "hammock theory" still work on and preferred DF to be the critical structure (Figure-1, 2 and Figure -4), which could uplift vesicourethral anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recently updated systematic review and Metaanalysis showed several advantages for MUS, traditional Burch colposuspension and autologous fascial slings still have their status and indications. [8][9][10] New guidelines state that these are all the same. [11] Invited Commentary…”
mentioning
confidence: 99%
“…Recently, serious complications from synthetic materials in MUS and POP mash repair have aroused certain controversy, which has prompted professionals to reappraise it. Although a recently updated systematic review and Meta-analysis showed several advantages for MUS, traditional Burch colposuspension and autologous fascial slings still have their status and indications [8–10] . New guidelines state that these are all the same [11]…”
mentioning
confidence: 99%